2018
DOI: 10.1097/prs.0000000000004023
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of the Use of Magnetic Resonance Imaging in the Diagnosis and Treatment of Wrist Soft Tissue Injury

Abstract: The provider must carefully consider the pretest probability of ordering a study that will affect treatment recommendation. Injudicious screening with magnetic resonance imaging ($15,565) incurred a cost nearly seven times the cost of the one imaging scan ($2246) before impacting one treatment recommendation. In the current era of cost containment and bundled payment, diagnostic test probability must be appreciated to guide physician ordering practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Further, orthopedic trauma, post-op, or post-splinting X-ray gave little to no change in management [ 162 169 ]. MRI of the wrist in ligamentous injury changed the surgical plan in 28% of patients and was thus low-value for many patients [ 170 ]. On general use of imaging in the musculoskeletal system, four studies showed that skeletal CT for peri-articular fractures (post-op) [ 171 ], and long bone cartilaginous lesions (also MRI) [ 172 ] were of low-value.…”
Section: Resultsmentioning
confidence: 99%
“…Further, orthopedic trauma, post-op, or post-splinting X-ray gave little to no change in management [ 162 169 ]. MRI of the wrist in ligamentous injury changed the surgical plan in 28% of patients and was thus low-value for many patients [ 170 ]. On general use of imaging in the musculoskeletal system, four studies showed that skeletal CT for peri-articular fractures (post-op) [ 171 ], and long bone cartilaginous lesions (also MRI) [ 172 ] were of low-value.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon may be beneficial to patients and the health care system as a whole, because MRI studies ordered by orthopedic surgeons are more likely to be cost-effective and positively influence their ultimate treatment plans. 15 Better knowledge of wrist anatomy and pertinent physical examination findings may also explain the higher utilization of arthrograms among orthopedic and hand surgeons. Surgeons are more inclined to use MRI to confirm a specific injury than to use it as a screening tool for wrist pain, 15 and an arthrogram may better help the surgeon delineate whether a patient requires operative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…15 Better knowledge of wrist anatomy and pertinent physical examination findings may also explain the higher utilization of arthrograms among orthopedic and hand surgeons. Surgeons are more inclined to use MRI to confirm a specific injury than to use it as a screening tool for wrist pain, 15 and an arthrogram may better help the surgeon delineate whether a patient requires operative treatment. Additionally, negative results on a highly sensitive test such as an MRA may be helpful in avoiding unnecessary operations.…”
Section: Discussionmentioning
confidence: 99%
“…Specialized clinical evaluation and a multidisciplinary, multimodality approach are proven to enhance the positive predictive value and cost effectiveness of MRI in postoperative settings of the wrist and hand. 72 In the presence of orthopaedic implants, basic and advanced metal artifact reduction techniques improve the image quality. 2,[36][37][38][39]73,74 Fig.…”
Section: Postoperative Mrimentioning
confidence: 99%